Public Choice Analyses of American Economic History Volume 1 (Studies in Public Choice, 2018)
This book - the first of two volumes- looks at episodes in American economic history from a public choice perspective. Each chapter discusses citizens, special interests, and government officials responding to economic incentives in both markets and politics. In doing so, the book provides fresh insights into important periods of American history, from the Acadian expulsion in 1755 to the allocation of government grants during the New Deal. This volume features the work of prominent economic historians such as Dora Costa, John Wallis, and Jeremy Atack; well-known public choice scholars such as Jac Heckelman; and younger scholars such as Vincent Geloso and Philip Magness. This book will be useful for researchers and students interested in economics, history, political science, economic history, public choice, and political economy. .